Interplay between phytohormone signalling pathways in plant defence – other than salicylic acid and jasmonic acid. Issue 5 (30th September 2022) - Gilroy, Eleanor; Breen, Susan
Abstract: Phytohormones are essential for all aspects of plant growth, development, and immunity; however, it is the interplay between phytohormones, as they dynamically change during these processes, that is key to this regulation. Hormones have traditionally been split into two groups: growth-promoting and stress-related. Here, we will discuss and show that all hormones play a role in plant defence, regardless of current designation. We highlight recent advances in our understanding of the complex phytohormone networks with less focus on archetypal immunity-related pathways and discuss protein and transcription factor signalling hubs that mediate hormone interplay.